2021
DOI: 10.21203/rs.3.rs-244297/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inadequate Use of Antibiotics in the Covid-19 Era: Effectiveness of Antibiotic Therapy

Abstract: Background: Since December 2019, the COVID-19 pandemic has changed the concept of medicine. This work aims to analyze the use of antibiotics in patients admitted to the hospital due to SARS-CoV-2 infection. Methods: This work analyzes the use and effectiveness of antibiotics in hospitalized patients with COVID-19 based on data from the SEMI-COVID-19 registry, an initiative to generate knowledge about this disease using data from electronic medical records. Our primary endpoint was all-cause in-hospital mortali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
1
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 65 publications
0
11
1
6
Order By: Relevance
“…Despite the fact that information on antibiotic regimes was not included in the interim Malaysian guidelines for clinical management of COVID-19 [ 16 ], the choices of antibiotic usage for COVID-19 patients with suspected bacterial co-infection were as recommended in the Malaysian National Antibiotic Guideline 2019 for pneumonia [ 30 ]. In Spain, amoxicillin and amoxicillin/clavulanic acid were the favourites (72.0%) [ 31 ], but they were prescribed at a higher rate in comparison with our study (37.8 to 56.7%). Although ceftriaxone was the second most common antibiotic used among COVID-19 patients in other countries such as the United States and Bangladesh, where it was prescribed at a rate of nearly 54.0% [ 10 , 32 ], the usage was low in this study (12.3%).…”
Section: Discussioncontrasting
confidence: 74%
“…Despite the fact that information on antibiotic regimes was not included in the interim Malaysian guidelines for clinical management of COVID-19 [ 16 ], the choices of antibiotic usage for COVID-19 patients with suspected bacterial co-infection were as recommended in the Malaysian National Antibiotic Guideline 2019 for pneumonia [ 30 ]. In Spain, amoxicillin and amoxicillin/clavulanic acid were the favourites (72.0%) [ 31 ], but they were prescribed at a higher rate in comparison with our study (37.8 to 56.7%). Although ceftriaxone was the second most common antibiotic used among COVID-19 patients in other countries such as the United States and Bangladesh, where it was prescribed at a rate of nearly 54.0% [ 10 , 32 ], the usage was low in this study (12.3%).…”
Section: Discussioncontrasting
confidence: 74%
“…For this reason, antimicrobial treatment is now prescribed earlier, and broad-spectrum antibiotics has been more frequently used in patients with suspected UTI in order to avoid severe infections and hospitalizations. Recently, Bendala Estrada et al demonstrated in a multicenter, retrospective study, that the overall percentage of bacterial co-infection among patients with COVID-19 was low, but the use of antibiotics was high [4]. Moreover, the Uro 2022, 2 56 recent International Severe Acute Respiratory and Emerging Infections Consortium (IS-ARIC) report demonstrated that 62% of patients with COVID-19 had received antimicrobial therapy, even though the prevalence of bacterial infections in COVID-19 has been low [5].…”
Section: Background and Aimsmentioning
confidence: 99%
“…W tych ostatnich przypadkach wyniki badań pochodzą nie tylko z badań in vitro, lecz także u pacjentów. Do wy-ników tych należy więc podejść z dużą ostrożnością [16,17]. Jak wskazano na wstępie, szczepionki nie powinny być traktowane ani łagodniej, ani bardziej restrykcyjnie niż wiele produktów na rynku.…”
Section: Adres Do Korespondencjiunclassified